Severe postpartum haemorrhage at a large referral hospital in Uganda: A prospective observational pilot study - Mia Appelbäck; Clare Lubulwa; Lawrence Kazibwe; Knut Haakon Stensæth; Thorkild Tylleskar; Josaphat Byamugisha (PLoS ONE, 2025)
Background Postpartum haemorrhage (PPH) is a leading cause of maternal mortality, near-misses and morbidity in Uganda and globally. Kawempe National Referral Hospital (KNRH), Uganda’s largest obstetric referral hospital, receives many obstetric emergencies, including PPH, from lower-level health facilities. Little is known about the outcomes and management of severe PPH at KNRH. This study aimed to map the occurrence, profile and management challenges of severe PPH at KNRH. Methods A prospective hospital-based observational pilot study was conducted between 5th April and 30th May 2023 at KNRH. Sixty women with severe PPH, both in-house and referrals, were enrolled. Data collection was done by research assistants on day 0–3 and 42 of inclusion, capturing characteristics, management and outcomes of the participants. Descriptive statistics were used for analysis. Results Of the 60 participants, 47 were referrals. There were 3 maternal deaths, 56 maternal near-misses (hysterectomy, cardiovascular dysfunction, uterine rupture or massive blood loss, and 46 underwent critical interventions (intensive care, laparotomy or blood transfusions). All the participants with uterine ruptures and 12 out of the 13 participants with stillbirths and hysterectomies, respectively, were among referrals. Only referrals had an initial systolic blood pressure ≤ 60 mm Hg and received ≥ 5 units of blood. In both groups approximately two thirds received tranexamic acid and oxytocin/misoprostol while few of the participants (23.3%) received uterine massage. Nine women had surgical site infections (8 were referrals), and 15 had suboptimal (fair/poor) wellbeing at 6 weeks postpartum (13 were referrals). None of the comparisons were statistically significant due to too few observations. Conclusions Referrals were more critically ill and disproportionally affected by adverse outcomes and substandard care. While drugs and fluids were often timely administered according to national guidelines and did not differ greatly between the groups, gaps remained particularly non-pharmaceutical interventions. Bettered implementation of evidence-based PPH management and strengthening of the referral system could improve quality of care and maternal outcomes.